2011
DOI: 10.2166/wst.2011.358
|View full text |Cite
|
Sign up to set email alerts
|

Bioplastic production using wood mill effluents as feedstock

Abstract: Fibreboard production is one of the most important industrial activities in Galicia (Spain). Great amounts of wastewater are generated, with properties depending on the type of wood, treatment process, final product and water reusing, among others. These effluents are characterized by a high chemical oxygen demand, low pH and nutrients limitation. Although anaerobic digestion is one of the most suitable processes for the treatment, lately bioplastics production (mainly polyhydroxyalkanoates) from wastewaters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The acidification efficiency of that waste stream was 37%. Ben et al (2011) obtained similar acidification efficiency from wood mill effluents (37e42%). As expected, the subsequent PHA content was low (25e29% of VSS).…”
Section: 2mentioning
confidence: 65%
See 3 more Smart Citations
“…The acidification efficiency of that waste stream was 37%. Ben et al (2011) obtained similar acidification efficiency from wood mill effluents (37e42%). As expected, the subsequent PHA content was low (25e29% of VSS).…”
Section: 2mentioning
confidence: 65%
“…Butyrate and acetate were the two dominant VFAs after acidification, which is similar to the results reported by Bengtsson et al (2008a) when acidifying paper mill wastewater. Besides acidifying paper mill wastewater, the result of other agroindustrial wastewater acidification have also been reported (Albuquerque et al, 2007;Ben et al, 2011;Coats et al, 2011;Dionisi et al, 2005;Morgan-Sagastume et al, 2010;Reddy and Mohan, 2012). Acetate was generally reported as the most abundant fermentation product.…”
Section: Volatile Fatty Acids Spectrum Of Acidificationmentioning
confidence: 91%
See 2 more Smart Citations
“…A wide range of substrates can be found within the wastes and/or wastewaters studied for PHA production. They include molasses (a by‐product of sugar production), urban wastewater, olive oil mill effluents, paper mill effluents, wood mill effluents, palm oil mill effluents and waste carbon . So far, brewery wastewater has not been used for PHA production using a system under aerobic dynamic feeding conditions.…”
Section: Introductionmentioning
confidence: 99%